Efficacy and safety of dual SGLT 1/2 inhibitor sotagliflozin in type 1 diabetes: meta-analysis of randomised controlled trials. (9th April 2019) - Musso, Giovanni; Gambino, Roberto; Cassader, Maurizio; Paschetta, Elena
Abstract: Objective: To assess the efficacy and safety of dual sodium glucose cotransporter (SGLT) 1/2 inhibitor sotagliflozin in type 1 diabetes mellitus. Design: Meta-analysis of randomised controlled trials. Data sources: Medline; Cochrane Library; Embase; international meeting abstracts; international and national clinical trial registries; and websites of US, European, and Japanese regulatory authorities, up to 10 January 2019. Eligibility criteria for selecting studies: Randomised controlled trials evaluating the effect of sotagliflozin versus active comparators or placebo on glycaemic and non-glycaemic outcomes and on adverse events in type 1 diabetes in participants older than 18. Three reviewers extracted data for study characteristics, outcomes of interest, and risk of bias and summarised strength of evidence using the grading of recommendations assessment, development, and evaluation approach. Main outcomes were pooled using random effects models. Results: Of 739 records identified, six randomised placebo controlled trials (n=3238, duration 4-52 weeks) were included. Sotagliflozin reduced levels of glycated haemoglobin (HbA1c; weighted mean difference −0.34% (95% confidence interval −0.41% to −0.27%), P<0.001); fasting plasma glucose (−16.98 mg/dL, −22.1 to −11.9; 1 mg/dL=0.0555 mmol/L) and two hour-postprandial plasma glucose (−39.2 mg/dL, −50.4 to −28.1); and daily total, basal, and bolus insulin dose (−8.99%, −10.93% to −7.05%; −8.03%, −10.14% to −5.93%; −9.14%, −12.17% to −6.12%; respectively). Sotagliflozin improved time in range (weighted mean difference 9.73%, 6.66% to 12.81%) and other continuous glucose monitoring parameters, and reduced body weight (−3.54%, −3.98% to −3.09%), systolic blood pressure (−3.85 mm Hg, −4.76 to −2.93), and albuminuria (albumin:creatinine ratio −14.57 mg/g, −26.87 to −2.28). Sotagliflozin reduced hypoglycaemia (weighted mean difference −9.09 events per patient year, −13.82 to −4.36) and severe hypoglycaemia (relative risk 0.69, 0.49 to 0.98). However, the drug increased the risk of ketoacidosis (relative risk 3.93, 1.94 to 7.96), genital tract infections (3.12, 2.14 to 4.54), diarrhoea (1.50, 1.08 to 2.10), and volume depletion events (2.19, 1.10 to 4.36). Initial HbA1c and basal insulin dose adjustment were associated with the risk of diabetic ketoacidosis. A sotagliflozin dose of 400 mg/day was associated with a greater improvement in most glycaemic and non-glycaemic outcomes than the 200 mg/day dose, without increasing the risk of adverse events. The quality of evidence was high to moderate for most outcomes, but low for major adverse cardiovascular events and all cause death. The relatively short duration of trials prevented assessment of long term outcomes. Conclusions: In type 1 diabetes, sotagliflozin improves glycaemic and non-glycaemic outcomes and reduces hypoglycaemia rate and severe hypoglycaemia. The risk of diabetic ketoacidosis could be minimised by appropriate patient selection and down-titration of the basal insulin dose.